Reframing the Role of the State in Religious Moderation: A Thematic Qur’anic Interpretation - Umar Kustiadi; Muhammad Ilham Sofyan; Mufarrih Yazid (SHAHIH: Journal of Islamicate Multidisciplinary, 2025)
The Thematic Interpretation of Religious Moderation (TTMA) published by the Indonesian Ministry of Religious Affairs in 2022 represents a significant shift in the discourse of religious moderation by explicitly integrating state-related concepts into Qur’anic interpretation. Unlike previous studies that predominantly frame moderation through ethical-religious principles such as wasathiyyah, ‘adl, and tasāmuh, TTMA reformulates moderation by incorporating state-oriented terms (ulū al-amr, balad, sha‘b, qawm), thereby constructing a distinctive state–religion synergy. This study addresses two central questions: (1) how are state principles articulated in TTMA’s interpretation of selected Qur’anic verses and (2) what conceptual model of the state’s role in religious moderation is proposed. Employing qualitative library research, his study analyzes TTMA’s Qur’anic interpretations using Talal Asad’s framework of discursive tradition and power to situate them within their socio-historical and political contex. The findings reveal three core state principles embedded in TTMA: national commitment, internalization of the state’s mediating role, and critical religious reasoning toward state authority. These principles collectively construct a moderation paradigm that emphasizes dialogical cooperation between religion and the state. This study contributes a novel perspective by showing that TTMA advances a moderate-humanist discourse positioning the state as an enabling actor in fostering religious harmony.